Transfer of pharmacopoeial liquid chromatography reversedphase methods for determination of related compounds in diclofenac sodium and metamizole sodium from conventional to core-shell column - Katerina Brezovska; Gabriela Petrovska; Jelena Acevska; Natalija Nakov; Ana Poceva-Panovska; Jasmina Tonic-Ribarska; Maja Hadzieva; Aneta Dimitrovska (University Ss Cyril and Methodius in Skopje, Faculty of Pharmacy and Macedonian Pharmaceutical Association, 2015)
Core-shell silica particles were developed as a new material for chromatographic stationary phases in order to provide fast and high efficiency separations of small and large molecules and complex samples, at pressures compatible with conventional HPLC equipment. The aim of our work was to show the applicability of the HPLC columns based on a core-shell technology for determination of related substances in diclofenac sodium and in metamizole sodium using the methods described in the corresponding monographs of the European pharmacopoeia. The obtained results have shown that the proposed methods can be successfully transferred on core shell column, with suitable adjustment of injection volume and flow rate. The advantage of using core-shell column is fast and highly efficient separation on conventional HPLC equipment with increased sensitivity of the method and high throughput of the analysis, providing enhanced lab productivity and reduced costs.